2023
DOI: 10.1038/s41467-023-37211-7
|View full text |Cite|
|
Sign up to set email alerts
|

Epigenetic and transcriptomic characterization reveals progression markers and essential pathways in clear cell renal cell carcinoma

Abstract: Identifying tumor-cell-specific markers and elucidating their epigenetic regulation and spatial heterogeneity provides mechanistic insights into cancer etiology. Here, we perform snRNA-seq and snATAC-seq in 34 and 28 human clear cell renal cell carcinoma (ccRCC) specimens, respectively, with matched bulk proteogenomics data. By identifying 20 tumor-specific markers through a multi-omics tiered approach, we reveal an association between higher ceruloplasmin (CP) expression and reduced survival. CP knockdown, co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 131 publications
0
14
0
Order By: Relevance
“…To identify the bacterial species with significantly changed relative abundances in mouse gut microbiota after the sonodynamic therapy, we analysed the fold of change, a widely used index in such analysis 60 , 61 , in bacterial relative abundance after the sonodynamic therapy relative to the healthy group (i.e., log 2 (Sonodynamic Therapy / Healthy)) (Fig. 7f ) and that relative to the control group (i.e., log 2 (Sonodynamic Therapy / Control)) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To identify the bacterial species with significantly changed relative abundances in mouse gut microbiota after the sonodynamic therapy, we analysed the fold of change, a widely used index in such analysis 60 , 61 , in bacterial relative abundance after the sonodynamic therapy relative to the healthy group (i.e., log 2 (Sonodynamic Therapy / Healthy)) (Fig. 7f ) and that relative to the control group (i.e., log 2 (Sonodynamic Therapy / Control)) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…High EMT enrichment scores on bulk RNA sequencing are associated with worse disease specific survival in ccRCC 22 , and various EMT ligand-receptor pairs have been implicated. 23, 24,25 Prior spatial transcriptomic work using spot-based resolution has also identified EMT-rich tumor cells being associated with worse prognosis in the TCGA cohort. 26 Still, specific ligand-receptor pairs from the EMT pathway were not elucidated in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, reduced accessibility of glucocorticoid receptor binding sites was observed in the proximal tubule of diabetic humans 15 . Investigations have also examined chromatin accessibility in human Papillary RCC (pRCC), kidney organoid differentiation 5 , 17 , 18 , and in multiple murine models 19 , 20 . Each of these studies provides important insights into epigenetic expression regulation in the kidney.…”
Section: Introductionmentioning
confidence: 99%